2017
DOI: 10.14233/ajchem.2017.20724
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Flavone of Excoecaria agallocha in Cytotoxicity Studies Using Hela Cells

Abstract: In this study, the compound flavone of mangrove plant Excoecaria agallocha was subjected to cytotoxicity studies using Hela cells was produced from ATCC, stock cells was cultured in Dulbecco's Modified Eagle medium (DMEM) supplemented with 10 % inactivated fetal bovine serum (FBS), penicillin (100 IU/mL), streptomycin (100 µg/mL) in an humidified atmosphere of 5 % CO2 at 37 ºC until confluent. The cell was dissociated with trypsin phosphate versene glucose (TPVG) solution (0.2 % trypsin, 0.02% EDTA, 0.05 % glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Cytotoxicity assays showed that sorafenib is a potent toxicant to cells in both lines, but stigmasterol cytotoxicity was weak; an IC 50 was not estimated since even high concentrations did not cause 50% lethality. Previous studies reported similar results for sorafenib [19] and stigmasterol [20] cytotoxicity in breast cancer.…”
Section: Discussionsupporting
confidence: 74%
“…Cytotoxicity assays showed that sorafenib is a potent toxicant to cells in both lines, but stigmasterol cytotoxicity was weak; an IC 50 was not estimated since even high concentrations did not cause 50% lethality. Previous studies reported similar results for sorafenib [19] and stigmasterol [20] cytotoxicity in breast cancer.…”
Section: Discussionsupporting
confidence: 74%
“…Rajeswari et al . ( 27 ) also reported that the flavone molecule from Excoecaria agallocha has the cytotoxic activity against HeLa cells.…”
Section: Resultsmentioning
confidence: 94%
“…To this 20 µL of MTT (2 mg/mL MTT in PBS) was added and further incubated for 4 hours at room temperature in a 5% CO 2 environment. About 100 µL DMSO was gently mixed into the plate to dissolve the formazan and absorbance read at 570 nm (15).…”
Section: In-vitro Cytotoxic Activity By Mtt Assaymentioning
confidence: 99%